The role of hedge funds in the asset pricing: evidence from China. Issue 2 (22nd January 2022) - Zhang, Jing; Zhang, Wei; Li, Youwei; Feng, Xu
Abstract : We document that hedge funds nurture mispricing in the Chinese financial market. We examine the relationship between hedge fund holdings and the degree of mispricing, assuming that hedge funds' stock holdings are mainly for arbitrage and not for hedging. We also examine this relationship with and without short-selling restrictions. Hedge funds intentionally hold overvalued stocks. Their trades, which generate an abnormal return of 1.78% per month, also impede the dissipation of stock mispricing. Furthermore, we find that trend-chasing may explain why hedge funds prefer to hold overvalued stocks. This research provides a new perspectives on the information content and potential investment value of hedge fund holdings in emerging markets.